(untitled) (Journal of the Bangladesh Agricultural University, 2014)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during the period from July to December 2012 to observe the effect of variety, age of tiller seedling used for transplanting and nitrogen management on the yield performance of transplant Aman rice. The experiment consisted of two varieties viz. BRRI dhan49 and BRRI dhan51, two ages tiller seedling viz. 25- and 35-day old, five nitrogen management viz. control (no urea), application of prilled urea @ 215 kg ha-1 (1/2 at 15 DAT+1/2 at 30 DAT), prilled urea @ 215 kg ha-1 (1/3 at 15DAT+1/3 at 30DAT+1/3 at 45DAT ), urea super granules (USG) 1.8 g and USG 2.7 g four-hill-1 in every alternate row. The experiment was laid out in randomized complete block design with three replications. The results revealed that higher plant characters, straw yield and harvest index were obtained from BRRI dhan49 compared to BRRI dhan51. Older seedlings (35-day old) produced higher grain yield to younger seedlings. The highest yield contributing characters and grain yield were obtained when 1.8g USG was applied. The grain yield was highest in 35-day old tiller seedlings of BRRI dhan51 while fertilized with 1.8g USG. This value was lowest when 25-day old tiller seedlings of BRRI dhan51 were fertilized with prilled urea in two split applications. It may be concluded that 35-day tiller seedlings of BRRI dhan51 fertilized with USG 1.8 g four-hill-1 could be used for achieving higher yield of transplant Aman rice. DOI: http://dx.doi.org/10.3329/jbau.v11i2.19903 J. Bangladesh Agril. Univ. 11(2): 249-256, 2013